Role of civil society organisations in the realisation of human rights in Africa and the effect of regulatory mechanisms on their functions : Ethiopia and Ghana perspective - Dowuona-Hammond, Christine (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.